2013
DOI: 10.3892/mmr.2013.1639
|View full text |Cite
|
Sign up to set email alerts
|

miR-218 is downregulated and directly targets SH3GL1 in childhood medulloblastoma

Abstract: An increasing number of studies have suggested that microRNAs (miRNAs) are aberrantly expressed in numerous types of tumors and that a deregulation in miRNA expression may lead to carcinogenesis. Although miR‑218 has been demonstrated to be downregulated in several types of cancer, including medulloblastoma (MB), its involvement in MB is unclear. In the present study, the expression of miR‑218 and SH3GL1 were assessed in four MB cell lines and normal cerebellum by qPCR. The ectopic expression of miR‑218 induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
4
7
0
1
Order By: Relevance
“…Indeed, we con rmed that the expression of miR-218 is decreased by 50% in primary tumours and by ~ 70% in recurrent GBM tumours. Decreased miR-218-5p expression levels have also been reported in other types of human cancer, such as medulloblastoma, thyroid cancer and cervical cancer [43][44][45]. We con rmed that the predicted miR-218 targets, the ECM components TN-C and SDC-2, are directly regulated by miR-218.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, we con rmed that the expression of miR-218 is decreased by 50% in primary tumours and by ~ 70% in recurrent GBM tumours. Decreased miR-218-5p expression levels have also been reported in other types of human cancer, such as medulloblastoma, thyroid cancer and cervical cancer [43][44][45]. We con rmed that the predicted miR-218 targets, the ECM components TN-C and SDC-2, are directly regulated by miR-218.…”
Section: Discussionsupporting
confidence: 67%
“…In agreement with that report, it was determined that miR-218 was expressed at a reduced level in osteosarcoma, compared with osteoblast cells. Previous studies demonstrated that miR-218 may serve a role in tumor suppression through targeting BMI1 (17,23), RET (18), tumor protein D52 (22), KIT (24) and SH3 domain-containing growth factor receptor bound protein 2-like protein 1 (25). Furthermore, it was determined that miR-218 directly targeted the E2F2 3'UTR in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…LASP1 is up-regulated in bladder [71] and prostate [72] cancer tissues, while SH3GL1 is overexpressed in childhood medulloblastoma [73]. They were both significantly suppressed by miR-218, which inhibited cell migration and invasion in cancer cells.…”
Section: Focal Adhesion Pathwaymentioning
confidence: 98%